Ready for the changes? Exploring EAP teachers’ competencies and training needs in tertiary level in China - Chen, Yu (Frontiers in Education, 2026)
English for academic purposes (EAP) has become increasingly prominent in tertiary education in China, as the focus of college English is shifting from general language proficiency toward supporting students’ academic studies and research engagement. Particularly in the digital era of teaching and learning, the expectations placed on teachers have become more diverse, further underscoring the need for targeted preparation and support. With this growing importance, greater attention is now being given to the professional preparation and development of EAP teachers. This study aimed to identify the challenges TEAP (Teacher of English for Academic Purposes) face in EAP implementation, examine the competencies required for their roles, and propose suggestions for TEAP training and education in China. A mixed method was designed to address this issue. Questionnaires were first presented to 21 EAP teacher participants to collect their demographic information and their perceptions of key aspects of EAP courses, including course scheduling, instruction methods, teachers’ competence and requirements. This was followed by semi-structured interviews with the same group of teachers, and the data were analyzed thematically. The findings of this research highlight the diverse responsibilities of EAP teachers, the challenges they face in the transformation from teachers of EGP to EAP. Moreover, insights are provided into EAP teacher training and professional development. The success of EAP will rely on a systematic and sustainable approach to teacher education and professional support.